The Rhetoric of Nature: Marvell and the Longinian Sublime - Strombergsson-DeNora, Adam Patrick (Université d'Ottawa / University of Ottawa, 2018)
This thesis examines Andrew Marvell’s politics through the lens of his competitive ethos, which I propose draws on values expressed in Peri hypsous, a third-century Greek treatise on rhetoric. The investigation reads Marvell’s early lyrics in order to demonstrate this ethos at work long before he openly enters politics. Marvell’s later political writings may instead be viewed as a logical conclusion to a long quest for the kind of High style that Peri hypsous recommends. This progression begins just after Marvell returns from his tour of the continent in 1648, with two poems that associate him with the Stanley Circle and, especially, John Hall, who produces a translation of Peri hypsous in 1652. Marvell’s association with Hall is reflected in the poems that both produce. The similarities between Marvell’s poetry and Longinian thought are further adduced. I contend that Marvell’s quest works through Plato’s “Ladder of Love” as this is expressed first in his Mower poems, then in his consideration of love, and finally in his view of statesmen’s households. The poetry displays a critical mind ready to deploy its knowledge of great writers that have come before. I argue that Marvell’s later confidence in his political prose stems from this earlier poetry, which reveals an intense curiosity about the languages of social interaction (of which politics is but a part). His poems thus viewed are more fundamentally political than has been understood and form an essential prologue to the political prose that so coloured his later fame.
Keywords: Andrew Marvell; Sublime; Literary History; Early-Modern Literature; John Hall; Rhetoric